New records of water mites of the genus Monatractides K. Viets (Acari: Hydrachnidia: Torrenticolidae) from Turkey - Peši?, Vladimir; Erman, Orhan; Esen, Yunus (My University, 2006)
New records of water mites of the genus Monatractides K.Viets (Acari: Hydrachnidia, Torrenticolidae) for the fauna of Turkey are presented in this study. Three species, Monatractides lusitanicus (Lundblad, 1941), M. aberratus (Lundblad, 1941), and M. vafael Peši? 2004, are reported for the first time from Turkey. © TÜBİTAK.
Keywords: Monatractides; New records; Running water; Turkey; Water mites